2020
DOI: 10.1186/s13046-020-01799-1
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA_0000392 promotes colorectal cancer progression through the miR-193a-5p/PIK3R3/AKT axis

Abstract: Background Circular RNAs (circRNAs), important members of the noncoding RNA family, have been recently revealed to play a role in the pathogenic progression of diseases, particularly in the malignant progression of cancer. With the application of high-throughput sequencing technology, a large number of circRNAs have been identified in tumor tissues, and some circRNAs have been demonstrated to act as oncogenes. In this study, we analyzed the circRNA expression profile in colorectal cancer (CRC) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 42 publications
0
90
0
Order By: Relevance
“…CircRNAs are known to exert their functions through sponging miRNAs and subsequently regulating downstream genes expression in cells ( 19 , 20 ). RegRNA2.0 ( ) was therefore used to predict the potential miRNA associated with circCCDC66.…”
Section: Methodsmentioning
confidence: 99%
“…CircRNAs are known to exert their functions through sponging miRNAs and subsequently regulating downstream genes expression in cells ( 19 , 20 ). RegRNA2.0 ( ) was therefore used to predict the potential miRNA associated with circCCDC66.…”
Section: Methodsmentioning
confidence: 99%
“…CircRNA has been reported to regulate CRC process. 29,30 Therefore, exploring the regulatory mechanism of CRC by circRNAs is necessary to search drug in treating CRC. CircRNAs were unveiled to mainly act as a carcinogen in CRC progression.…”
Section: Discussionmentioning
confidence: 99%
“…The level of expression of circRNAs has specificity in species, tissue, and time (22). More research reports have shown that circRNAs are involved in the development of malignant tumors, and a group of circRNAs is specifically involved in signal regulation in the process of colorectal cancer (23)(24)(25). Moreover, a group of circRNAs was found to be abnormally expressed in hepatocellular carcinoma (HCC) (26)(27)(28), enabling the early detection of liver cancer.…”
Section: Discussionmentioning
confidence: 99%